A Qualitative Study on the Implementation of Academic Information System Management (SINKAD) in Enhancing Educational Administration Efficiency at Wearnes Malang - Fahmi Affan (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
This study aims to analyze the implementation of Academic Information System (SINKAD) management in improving the efficiency of educational administration at Wearnes Education Center Malang. Before the implementation of SINKAD, administrative activities such as grade input, student registration, and schedule management were carried out manually, which often caused delays and data errors. This research employs a qualitative method with a case study approach, using interviews, observations, and documentation involving administrative staff and system users. The results of the study indicate that the implementation of SINKAD has had a positive impact on work efficiency and administrative services. Administrative processes that previously required 60–90 minutes can now be completed within 15–25 minutes. In addition, data accuracy has improved, interdepartmental coordination has become more effective, and student services are faster and more transparent. The study concludes that effective SINKAD management enhances the effectiveness and efficiency of educational administration and supports professional academic governance at Wearnes Malang.